Perkuatan Sambungan Perpanjangan Batang Kayu Resak Dengan Kombinasi Baut Dan Perekat Epoxy - Saputra, Yogi; Fakhri, Fakhri; Kamaldi, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Resak is local wood originated from Indonesia, this wood is classified as class II for its strength and class III for its durability according to (PKKI 1961 NI-5). Three type of connections were observed in this study, they were U1, U2, and U3. U1 was the bolt connection, U2 was the combination of bolt with adhesive on the slice plane, while U3 wasthe combination of bolt with adhesive on the bolt hole. This study oins to study the shear strength of wood connection with respective connection models by being tested using a tool Universal Testing Machine (UTM). The test results showed that the shear strength of the thecombination of bolt with adhesive on the slice plane showed a strength increase of about + 31.02%. For the combination of bolt with adhesive on the bolt hole did not increase, even decreased by -13.86%. the connection bolt and adhesive connection in the slice plane show good gluing performance making it suitable for large capacity connection designs and increase connection reinforcement.Keywords: Wood resak, reinforcement joints, extension joints, bolts, epoxy adhesives.